Electromechanical properties of multi-walled carbon nanotube/gelatin hydrogel composites: Effects of aspect ratios, electric field, and temperature - Tungkavet T. (Elsevier Ltd, 2014)
The effects of multi-walled carbon nanotube (MWNT) aspect ratio, electric field strength and temperature on the electromechanical properties of MWNT/gelatin hydrogel composites were investigated. The highest aspect ratio of MWNT provides the composites with the highest dynamic moduli under electric field. The MWNT/gelatin hydrogel composites of 0.01, 0.1, 0.5, and 1 vol.% and the pure gelatin hydrogel possess the storage modulus sensitivity values of 0.69, 1.23, 0.94, 0.81 and 0.47, respectively, at 800 V/mm. The results can be interpreted in terms of the enhanced polarizability between the carboxyl groups of gelatin under the presence of MWNT. The effect of temperature on the electromechanical properties of MWNT/gelatin hydrogel composites investigated between 30 °C and 90 °C shows three distinct regimes of temperature-dependent storage modulus behavior. In the deflection testing, the effects of electric field on the deflection distance and the dielectrophoresis force of the MWNT/gelatin hydrogel composites were also investigated. MWNT/gelatin hydrogel composites suspended in the silicone oil between electrodes, respond rapidly with a deflection toward the anode site, indicating the attractive force between anode and the polarized carboxyl group as the gelatin structure possesses negative charges.